COST ANALYSIS OF TAXANE-BASED AND CISPLATIN-BASED CHEMOTHERAPY REGIMENS FOR EPITHELIAL OVARIAN CANCER IN DHARMAIS NATIONAL CANCER HOSPITAL - Dwipoyono, Bambang; Choirunisa, Septyana; Nadjib, Mardiati; Sjaaf, Amal C (International Journal of Applied Pharmaceutics, 2017)
Objective: This exploratory study aimed to evaluate and compare the treatment costs of taxane-based versus cisplatin-based chemotherapy. Methods: This study used data from the medical and financial records of ovarian cancer patients who were admitted to Dharmais National Cancer Hospital (RSKD) between 2008 and 2012 and subsequently underwent surgery and were treated with chemotherapy. Data were analyzed using descriptive analysis, and a Kaplan–Meier graph was plotted to compare the survival of the patients in the taxane-based and cisplatin-based chemotherapy groups. Results: Of 41 patients, treatment costs were available for nine patients who had undergone taxane-based chemotherapy and for 31 patients who had undergone cisplatin-based chemotherapy. In general, surgical procedures accounted for the highest proportion of the treatment costs, followed by chemotherapy. Taxane-based chemotherapy (six cycles) was 4 times more expensive than cisplatin-based therapy. The pre- and post-chemotherapy costs of care among those treated with the taxane-based regimen were 3-4 times more expensive than those of the patients who received cisplatinbased treatment. The disease-free recurrence duration of the patients treated with taxane was longer (median=18 months) than that of the patients treated with cisplatin (median=5 months). Conclusions: Taxane-based therapy increased the disease-free recurrence duration of the patients, with disease-free recurrence 3 times longer than that of the patients treated with the cisplatin-based regimen. However, the treatment costs of the taxane-based regimen were 4 times higher than those of the cisplatin-based treatment.